Peru : Review Under the Flexible Credit Line Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Peru. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Peru's very strong macroeconomic policies and institutional policy frameworks have helped anchor strong growth and stability over the past several years and navigate the challenges posed by the COVID-19 pandemic. The confluence of a sound inflation-targeting regime, flexible exchange rate, credible fiscal framework, reflected in very low public debt, and sound financial sector supervision and regulation have allowed the country to deploy a robust policy response to mitigate the socio-economic impact of the pandemic while sustaining strong access to international capital markets. Following the worst economic contraction in 30 years, economic activity is expected to rebound this year as COVID-19 vaccines are rolled out, and the pandemic is gradually brought under control. Real GDP is expected to return to its pre-pandemic level by 2022, supported by improved terms-of-trade and a pick-up in domestic demand. The second round of presidential elections is scheduled for June 6.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Peru